Relentless - Koontz, Dean R. (Dean Ray), 1945- (New York : Random House Large Print, 2009)
Cubby Green is a bestselling novelist who gets a vicious and inaccurate review from seldom seen critic Shearman Waxx. Cubby finds out where Waxx has lunch and soon finds himself in a desperate struggle with a relentless sociopath, facing an inexorable assault on far more than his life.
Keywords: Novelists -- Fiction; Large type books; Critics -- Fiction